2006
DOI: 10.1002/app.23500
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(butylene terephthalate) nanocomposite fibers: Thermo‐mechanical properties and morphology

Abstract: Nanocomposites of poly(butylene terephthalate) (PBT) with the organoclay C 12 PPh-MMT were prepared using in situ intercalation polymerization. Hybrids with various organoclay contents were processed for fiber spinning to examine their thermal behavior, tensile mechanical properties, and morphologies for various draw ratios (DRs). The thermal properties (T g , T m , and T D i ) of the hybrid fibers were found to be better than those of pure PBT fibers and were unchanged by variation of the organoclay loading u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…[18][19][20] In recent years, PBT/silicate layer nanocomposites have been studied by numerous researchers because good dispersion of the silicate layer greatly improves the thermal properties, mechanical properties and heat distortion temperature for application in engineering plastics. [21][22][23][24][25][26] Chang et al 26 investigated the morphologies, mechanical properties, and crystallization behaviors of PBT/montmorillonite (MMT) nanocomposites. Good dispersion of clay in a PBT matrix leads to increase in the mechanical properties, dynamic mechanical properties, melt viscosity and non-isothermal crystallization rates in comparison with homo PBT.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] In recent years, PBT/silicate layer nanocomposites have been studied by numerous researchers because good dispersion of the silicate layer greatly improves the thermal properties, mechanical properties and heat distortion temperature for application in engineering plastics. [21][22][23][24][25][26] Chang et al 26 investigated the morphologies, mechanical properties, and crystallization behaviors of PBT/montmorillonite (MMT) nanocomposites. Good dispersion of clay in a PBT matrix leads to increase in the mechanical properties, dynamic mechanical properties, melt viscosity and non-isothermal crystallization rates in comparison with homo PBT.…”
Section: Introductionmentioning
confidence: 99%
“…In 2002, the use of nanoclays has emerged as an interesting way for developing multifunctional textiles when polyamide‐6 clay nanocomposite multifilament yarns were produced by Bourbigot et al6 Indeed, the authors demonstrated a decrease of about 40% of the heat release rate (HRR) of knitted structures made with polyamide‐6 nanocomposite compared to the virgin polyamide. Many researchers were therefore interested in the development of nanocomposite fibers based on several polymer matrices such as polyamide‐6 (PA‐6),7–9 polybutylene terephtalate (PBT),10–12 polytrimethylene terephtalate (PTT),13–15 polyethylene terephtalate (PET),14, 16, 17–20 polylactide (PLA),21, 22 polyethylene (PE)23, 24 or polyimideamide (PIA) 25, 26…”
Section: Introductionmentioning
confidence: 99%
“…Polymer nanocomposites comprised of a semicrystalline polymer matrix are particularly attractive due to the dramatic improvement in heat distortion temperature (HDT) and modulus provided by the nanoparticle reinforcement. Polymer/clay nanocomposites of most commodity semicrystalline thermoplastics such as nylon‐6,3, 4, 8 poly(ethylene terephthalate)9–14 (PET) and poly(butylene terephthalate)15–26 (PBT) have been studied in detail. Several articles and patents reports the preparation of nanocomposites of poly(alkylene terephthalate) 9–26.…”
Section: Introductionmentioning
confidence: 99%